Universalism in Welfare Policy: The Swedish Case beyond 1990 - Blomqvist, Paula (Social Inclusion, 2020)
Despite its broad usage, universalism as a concept is not always clearly defined. In this article, a multidimensional definition of universalism in social policy is developed, based on four policy characteristics: inclusion, financing, provision, and the adequacy of benefits. In the empirical part of the article, the feasibility of this definition is tested by an analysis of recent changes in the Swedish welfare state, which is typically described as universal but has undergone substantive reforms since 1990. Four social policy areas are examined: pensions, social insurance, health care, and family policy. The results indicate that Swedish welfare policies retain their universalistic character in some dimensions but have become less universalistic in others. This demonstrates that a multidimensional approach is best suited to capture in full the nature and implications of welfare state reform.